2014
DOI: 10.30843/nzpp.2014.67.5747
|View full text |Cite
|
Sign up to set email alerts
|

Effects of chemical and natural product treatments on bunch openness and botrytis bunch rot in Sauvignon blanc grapes

Abstract: Products containing different gibberellic acids (GA) and GA inhibitors were applied to grapevines during the 2009/10 and 2010/11 growing seasons to evaluate possible effects on bunch architecture and subsequent botrytis bunch rot (BBR) severity In the 2010/11 season the timing formulation and dose responses of the GA inhibitors in association with a biological control agent were also evaluated for their effects on BBR In both seasons the effects on yield and fruit quality and quantity were also measured to det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 12 publications
1
18
0
Order By: Relevance
“…Varieties with tight bunches are considered to be more susceptible to B. cinerea, not only because of compression among the berries, which can create wounds easily colonised by the pathogen, but also because of the intrinsically higher susceptibility of the epicuticular wax at the point of berry contact (Marois et al, 1986). The advantages of increasing bunch openness, achieved with the use of gibberellic acid, is still controversial (Ferree et al, 2003;Mundy et al, 2014) and bunch tightness should probably be considered in the wider context, being only one of the factors concurring in susceptibility to the disease in some varieties (Vail et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Varieties with tight bunches are considered to be more susceptible to B. cinerea, not only because of compression among the berries, which can create wounds easily colonised by the pathogen, but also because of the intrinsically higher susceptibility of the epicuticular wax at the point of berry contact (Marois et al, 1986). The advantages of increasing bunch openness, achieved with the use of gibberellic acid, is still controversial (Ferree et al, 2003;Mundy et al, 2014) and bunch tightness should probably be considered in the wider context, being only one of the factors concurring in susceptibility to the disease in some varieties (Vail et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…The concentrations of gibberellic acid and ProCa, as well as spray timing at full bloom, were chosen based on studies conducted in the United States, Luxembourg, and New Zealand, which reported effects of these growth regulators on cluster architecture and Botrytis bunch rot control (Ferree et al, 2003;Molitor et al, 2011;Mundy et al, 2014).…”
Section: Methodsmentioning
confidence: 99%
“…Botrytis bunch rot or gray mold, caused by the fungi Botryotinia fuckeliana (de Bary) Whetzel and Botrytis cinerea Persoon ex Fries in conidial form, is one of the most important grape diseases in the highland regions of Southern Brazil (Bem et al, 2017). This disease is a problem in regions with cool and wet macroclimates, and, in general, fungal infection is most likely to occur when clusters are dense and little exposed to the sun (Hed et al, 2009;Mundy et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gibberellin hormone plays a direct role in size and compactness of the clusters. It has been validated positive effect of gibberellin in reducing and increasing cluster compactness and size of berries, respectively [5,45]. One of the main factors in compactness of Sistan's Yaghooti grape and small size of berries is down regulation of GA gene which has a direct effect on reducing activity of gibberellin hormone in the process of grape cluster development.…”
Section: Accepted Manuscriptmentioning
confidence: 95%